A Collaborative Mass Customization Design Project on Electronic Consumer Goods - Kaygın Sel, Sultan; Pedgley, Owain (International Journal of Industrial Engineering and Management, 2012)
Mass customization in the electronic consumer goods industry can benefit from the vision of industrialdesigners to show what is achievable. To research these issues, a mass customization project was carried out with 36 undergraduate industrial design students working in collaboration with Vestel Electronics Company (one of the leading electronic consumer goods manufacturers in the world). Students were required to generate innovative product proposals for four product groups currently within Vestel’s design and manufacturing portfolio. The research findings are summarized with key principles for mass customization of electronic consumer goods and identification of problems and opportunities. Article history: Received (21 November 2012); Revised (01 December 2012); Accepted (05 December 2012)